Development of a supportive care needs eHealth application for patients with cervical cancer undergoing surgery: a feasibility study - Yongxia Song; Lili Xia; Xiaodi Ju; Wenjing Wang; Xiaoling Ge; Jingfang Hong (BMC, 2024)
Abstract Purpose To inform the development of an eHealth application for patients with cervical cancer for monitoring supportive care needs, perceived care supply and quality of life. Methods A mixed-method design was used. The 19-month process involved five phases: (1) a literature review to screen the components of applications, (2) a cross-sectional needs assessment for patients with cervical cancer to define the needs and application program frame, (3) expert consultation to refine the draft, (4) software development, and (5) pilot testing and user comment collection. Patients in the intervention group received a 7-day application intervention combined with usual care. Supportive care needs, perceived care supply, quality of life and user's additional comments were collected. Results The literature review results in phase 1 revealed the importance of full preparation, especially a supportive care needs assessment, before application development. Subsequent supportive care needs investigation in phase 2 revealed that the most urgent needs were informational needs and privacy protection. In phase 3, 43 expert recommendations for application improvement were refined. The new application contained the patient and the health care professional portal in phase 4. Then, on Day 7, there existed score changes of the outcome measures in both intervention and control group. Users had a positive experience with the application. Conclusions This study demonstrates the feasibility of applications targeting access to supportive care, which may be effective for improving the outcome measures but needed to be evaluated in future studies.